Generation of mineral density distribution maps from subject-specific models of mandibles - a preliminary study - Alister, Francisco; Ramos-Grez, Jorge Andrés; Vargas, Alex Patricio (The international journal of medical robotics + computer assisted surgery, 2012)
Background Determination of the mineral content of bone and its distribution by computed tomography (CT) enables one to define the insertion points for prosthetic devices, or determine the degree of healing in cases of fracture or surgical intervention. The use of subject‐specific models allows mapping of the spatial structure and the mineral content of the bone graphically and quantitatively. Methods Subject‐specific models and mineral density maps from pig jaws were developed using segmentation, transcription tools and finite element analysis software. This study considered six frozen heads from pigs aged 10–12 months, and phantom solutions of K2HPO4. The predicted bone mass of each jaw was compared with its respective ash mass after incineration. Results The tridimensional maps show highest density values at the molar cusp and within the symphysis. The average percentage error relative to the mineral density maps was −18.4%. The radiation dose was reduced by a factor of eight from the recommended maximum without compromising the precision of the models. Conclusions The computed tridimensional mineral density maps illustrate, numerically and graphically, the spatial distribution of the density field within the mandibular bone. These maps could facilitate the location of insertion points or determine the evolution of the mineralization level of a patient's bone tissue. Copyright © 2012 John Wiley & Sons, Ltd.